Pengaruh Nilai Investasi, Jumlah Unit Usaha Dan Upah Minimum Terhadap Permintaan Tenaga Kerja Industri Kecil Dan Menengah Di Provinsi Jawa Tengah - Tri Utami, Dian, Drs.Triyono, M.Si, Eni Setyowati, SE, M.Si (2016)
The Role of Small and Medium Enterprises (SMEs) from year to year is always an increase in demand for labor and reducing unemployment tenga with employment dicipataknnya. It can be seen from the average SME is able to absorb the labor force by 90% of the total workforce in Indonesia. This study was conducted to determine several factors: Investment Value, Total Business unit, and the Minimum Wage Employment (MSE) which may affect the demand for labor small medium industry in Central Java. The research sample is taken from a book java period 1993-2010 statistics published by the Central Statistics Agency (BPS). This study using multiple regression analysis (OLS) Full mode. Analysis results showed that the investment value significantly influence the employment sector Central Java, while the Total Business Unit and MSE no significant effect on labor demand sector of Small and Medium Industries in Central Java but both have a positive relationship. This study has a level of accuracy of 96.8% and the remaining 3.2% is influenced by other factors not examined.